Model testing of a floating wave energy converter with an internal U-shaped oscillating water column. (15th July 2021) - Ribeiro e Silva, S.; Gomes, R.P.F.; Lopes, B.S.; Carrelhas, A.A.D.; Gato, L.M.C.; Henriques, J.C.C.; Gordo, J.M.; Falcão, A.F.O.
Highlights: UGEN device hydrodynamic characterization carried out through experimental tests. Roll, sway and heave motions contribute for power extraction. Parametric resonance identified and showed potential for energy extraction. Slow drift and large heave motion generated highest load peaks in survivability tests. Abstract: The development of wave energy converters is centred on the combination of two factors: cost-effectiveness of energy extraction and system survivability on extreme sea conditions. Despite advances in numerical modelling, wave tank model testing still presents the most reliable option to evaluate these two factors. This paper presents an experimental study on the hydrodynamic responses of the UGEN, a wave energy converter consisting of an asymmetric floater with an internal U-shaped tank partially filled with water. The device absorbs energy through the oscillating-water-column (OWC) motion inside the U-shaped tank, induced by the wave action on the floater. The experimental testing of a bottom-moored 1:24th-scale model was performed at the COAST Laboratory, University of Plymouth, UK, considering regular and irregular wave conditions. The wave tank test measurements report six-degree-of-freedom rigid-body motions, mean drift forces, OWC motion, structural stresses and mooring loads. Results present the characterization of the energy absorption at the internal OWC induced by the floater's sway, heave and roll. The occurrence of low-cycle auto-parametric resonance under certain wave conditions was detected and induced large roll motions, which affected power extraction and increased mooring line loads, particularly for large wave amplitudes.